A study on the thermal and mechanical properties of composites made of nanolignocellulose and Pebax® polymer. (November 2019) - Farsi, Mohammad; Tavasoli, Afshin; Yousefi, Hossein; Tabari, Hassan Ziaei
This study aimed at producing the biodegradable composite from lignocellulose nanofibers (LCNFs) and Pebax ® thermoplastic elastomer. For this purpose, LCNFs at different levels of 0, 1, 3, and 5% were considered. The LCNFs were prepared by benzyl alcohol and then mixed with Pebax ® . The liquid phase of the LCNFs and soluble polymer was prepared and then the masterbatches were mixed in an internal mixer (Model 815802, Brabender, Germany). The mixtures from the internal mixer were put into a hot press and test samples were compress-molded. The physical properties results indicated that water absorption and thickness swelling decreased by the addition of more amount of LCNF. By the addition of LCNFs to polymer, the tensile strength and modulus and impact strength were increased compared to samples without LCNF. No regular trend of enthalpy changes was observed as the content of LCNF changed. When the LCNF concentration was increased to 5%, the crystallization temperature was increased. As the LCNF concentration increased to 3%, the glass transition temperature ( T g ) was decreased, whereas by incorporating more LCNFs, the T g was increased. The result of the Fourier transform infrared spectra showed the peaks at 1740 cm −1 which indicated the presence of polyamide bonds. Also, new peaks were observed in the range of 1400–1500 cm −1 that was probably related to the presence of C−C bonds of glucose at LCNFs chains.